THE IMPORTANCE OF REGULATING NON-CONCIVTION BASED FORFEITURE IN CORRUPTION CASES IN INDONESIA - Mukminah, Lily Solichul; Hartiwiningsih, Hartiwiningsih; Yudianto, Otto; Hufron, Hufron (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
This research examines the importance of regulating Non-Conviction Based Asset Forfeiture (NCB) in corruption cases in Indonesia. NCB is a mechanism of asset forfeiture that allows the state to seize assets without a prior criminal conviction. The study argues that the regulation of NCB is necessary to ensure the effectiveness of asset recovery in corruption cases and to prevent abuse of power by law enforcement agencies. The research uses a qualitative approach and analyzes relevant laws and regulations, court decisions, and academic literature. The findings suggest that the current legal framework for NCB in Indonesia is inadequate, leading to the misuse of NCB by law enforcement agencies. The research recommends the enactment of a specific law on NCB in corruption cases that provides clear criteria and safeguards for the use of this mechanism.